NILAI-NILAI EDUKATIF DALAM PERMAINAN TRADISIONAL PADA MASYARAKAT LOKAL DI SUMEDANG - Titin Yuniartin; Mumuh Muhtarom (Tatar Pasundan: Jurnal Diklat Keagamaan, 2019)
The purpose of compiling this article is to analyze the values of education in a variety of traditional games in the Sumedang community. The method used is descriptive analytical with analytical techniques through the study of meanings on symbols that appear in traditional games. The results of the discussion show that in traditional games are actually loaded with educational values for children as an effort to inherit the noble values that exist in the content of local culture. Thus it can be concluded that the values of education are basically universal despite appearing in the local face. Key Words: Education values; Local Culture; Traditional games